2017
DOI: 10.1371/journal.pone.0180787
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of the lactisole ‘Sweet Water Taste’ by sweeteners

Abstract: Pre-exposure to taste stimuli and certain chemicals can cause water to have a taste. Here we studied further the ‘sweet water taste’ (SWT) perceived after exposure to the sweet taste inhibitor lactisole. Experiment 1 investigated an incidental observation that presenting lactisole in mixture with sucrose reduced the intensity of the SWT. The results confirmed this observation and also showed that rinsing with sucrose after lactisole could completely eliminate the SWT. The generalizability of these findings was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…We also observed that efficiency of inhibition was influenced by the time of incubation. As shown by Alvarado et al, 49 sucrose to activate a signaling response. Thus, depending on the effects studied, shorter or longer stimulation periods might be considered to obtain optimal results in inhibition or enhancing assays respectively.…”
Section: Discussionmentioning
confidence: 90%
“…We also observed that efficiency of inhibition was influenced by the time of incubation. As shown by Alvarado et al, 49 sucrose to activate a signaling response. Thus, depending on the effects studied, shorter or longer stimulation periods might be considered to obtain optimal results in inhibition or enhancing assays respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Both sweet and umami taste signaling pathways are thought to share a common component, the GPCR T1R3. In humans, lactisole inhibits the perceived taste of both sweet [ 12 ] and umami [ 13 ] compounds at concentrations of >1 mM. Lactisole binds to the transmembrane domains of T1R3 where it interrupts T1R3-mediated Ca 2+ signaling [ 11 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lactisole has been shown to inhibit T1R3 through interactions with a binding pocket within T1R3′s transmembrane domain [ 11 ]. Once bound, lactisole inhibits the downstream Ca 2+ pathways activated by the detection of sweet [ 12 ] or umami molecules [ 13 ]. Consequently, in human taste signaling pathways, lactisole inhibits the detection of both sweet and savory molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms can be explained by the allosteric properties of the receptors and the different binding sites of the ligands at high and low concentrations. This supplementary binding induces loss of sweet perception (Alvarado et al, 2017;Galindo-Cuspinera et al, 2006). The activity of the TAS1R2/TAS1R3 agonist, miraculin, is dependent on both intracellular and extracellular pH with lower extracellular pH enhancing the sweetness sensation.…”
Section: Introductionmentioning
confidence: 99%